Considerations Regarding Graduate Student Persistence - Schinke, Robert J.; da Costa, José; Andrews, Michael (Alberta Journal of Educational Research, 2001)
Completion of graduate studies is a central issue for universities. Over the past decade researchers interested in higher education have become concerned with graduate student completion rates. Possible reasons underlying variations in graduate student persistence have included the amassed learning experiences and subsequent perceptions of graduate students, supervisory committee members, and other department staff. This article addresses some of the psychosocial considerations that underlie the complex interactions among students, supervisory committees, and departmental support staff, referred to here as the "academic triad." Using Seligman's (1991) explanatory framework and Bandura's (1986) self-efficacy theory, this article explains how student persistence is closely tied to the behavior of students, academics, and departmental support staff. Further, the article provides two frameworks to gain a broadened understanding of the relationship between the academic triad and graduate student persistence. Recommendations are provided as to how to foster graduate student persistence through improved personal and interpersonal reflexivity.